Religious Science and Scientific Religion: Reimagining Religion-Science Relations in Contemporary Indonesian Muslim Thought - Lutfi, Muhammad; Mukhammad Zamzami; Abd A’la; Khalimatu Nisa (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2025)
The COVID-19 pandemic has revealed the persistent tension between religion and science in Indonesia, as different perspectives have emerged on issues such as vaccination, restrictions on worship, and public health protocols. This moment of crisis underscores the broader epistemological gulf between religious belief and scientific reasoning, reigniting the debate about their respective roles in addressing existential and social challenges. Responding to this complex landscape, Haidar Bagir and Ulil Abshar Abdalla have articulated two conceptual frameworks of religious science and scientific religion that aim to redefine the relationship between religion and science. This article critically analyzes the arguments using John Haught’s taxonomy of conflict, contrast, contact, and confirmation. Haidar Bagir’s views emphasize respectful differentiation and dialogical engagement in the form of contrast and contact, while Ulil Abshar Abdalla envisions a more harmonious interaction that affirms mutual legitimacy in the form of confirmation. Both thinkers reject the absolutism of modern scientism and call for religious thought to be more responsive to scientific developments. This study highlights the urgency of fostering epistemological synergy so that religion and science can face the ethical and intellectual challenges of our time together.